RESEARCH OF MECHANICAL PROPERTIES OF ROCKS OF THE PREKARPATHIANS DEFLECTION - Слепко, Мирослав Миколайович; Чарковський, Віктор Маркович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Laboratory researches of a number of indicators of mechanical properties of rocks of the Precarpathians deflection are executed. Histograms of distribution of mechanical properties on summary indicators of laboratory measurements are submitted. Among indicators were defined: hardness on a stamp; abrasivity; module of elasticity and limit of elasticity; plasticity coefficient; specific volume and superficial power consumption of destruction. Change of indicators according to geological suites of the Precarpathians deflection is described. It is established that the hardness and the module of elasticity for sand stones considerably differ with geological suites what points three mode distribution of these indicators to. Functions of distribution for statistical modeling and research of influence of indicators of mechanical properties on technological processes of well-drilling are picked up.